The More, the Merrier…: The Effect of Social Network Heterogeneity on Attitudes Toward Political Opponents - Paulina Górska; Dominika Bulska; Maciej Górski (Social Inclusion)
Social network homogeneity is considered one of the key drivers of the rise in affective polarization. As opportunities for contact with different others decrease, out‐group animosity increases, fueling political conflict and destabilizing democracy. At the same time, research suggests that diverse social networks foster tolerance for opposing viewpoints. Consistent with the contact hypothesis, empirical studies show that individuals with more politically diverse networks hold more favorable attitudes toward their political opponents. However, it remains unclear whether network heterogeneity affects intergroup relations in the same way as intergroup contact or whether it represents a distinct source of depolarization. Furthermore, there is limited empirical evidence on the psychological mechanisms through which network heterogeneity influences attitudes toward political opponents. In this article, we address these gaps by presenting the results of a 2019 survey study (𝑁 = 378) conducted in Poland, within a highly polarized context. We show that having a more heterogeneous social network in terms of partisanship is indirectly related to more positive attitudes toward political opponents—an effect explained sequentially by diminished moral conviction and weakened party identification, as well as by weakened party identification alone. Contrary to what has been assumed, this effect is independent of traditionally operationalized intergroup contact, both in terms of its quantity and quality.